The effects of managerial ability on firm performance and the mediating role of capital structure: evidence from Taiwan - Ting, Irene Wei Kiong; Tebourbi, Imen; Lu, Wen-Min; Kweh, Qian Long (Springer, 2021)
This study utilizes mediation analysis and bootstrapping to analyze the mediating effect of capital structure on the association between managerial ability and firm performance. The dataset consists of 6384 firm-year observations from the Taiwanese electronics industry during 2005–2018. Our results indicate that (1) low (high) levels of debt are likely observed in firms with CEOs with high (low) ability, (2) managerial ability positively affects firm performance, and (3) capital structure mediates the positive relationship between managerial ability and firm performance. Overall, the findings may have limited generalizability due to the specific sample characteristics and provide convincing support for the importance of capital structure as a mediator in the managerial ability-firm performance nexus. Specifically, this study highlights the need for examining the effect of managerial ability on firm performance through a mediator.